2017
DOI: 10.4103/ijo.ijo_545_16
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative amplitude using the minus lens at different near distances

Abstract: Purpose:The purpose of this study was to compare the mean findings and the repeatability of the minus lens (ML) amplitude of accommodation (AA) at 33 cm and 40 cm.Materials and Methods:AA was measured from the dominant eye of 120 fully corrected subjects using the ML procedure when viewing the target at both 33 and 40 cm. Each measurement was repeated between 24 and 48 hours after the first trial.Results:Mean AA when tested at 33 cm and 40 cm was 10.20 diopter (D) (standard deviation [SD] =1.24) and 8.85 D (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The results of this study agree with the findings of Momeni-Maghaddam et al 11,12 who found that the AA measured at 33 cm was higher than that with the target at 40 cm, and the mean difference was 1.17 D on average. In this study, the mean difference between the AA measured using minuslens-to-blur method with the target at 40 cm and 33 cm was -0.70 ± 0.84 D. The minus lens technique is one of the subjective techniques for measuring the AA and like other subjective methods tends to overestimate the true AA, mainly due to depth of focus, target and pupil size and illumination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study agree with the findings of Momeni-Maghaddam et al 11,12 who found that the AA measured at 33 cm was higher than that with the target at 40 cm, and the mean difference was 1.17 D on average. In this study, the mean difference between the AA measured using minuslens-to-blur method with the target at 40 cm and 33 cm was -0.70 ± 0.84 D. The minus lens technique is one of the subjective techniques for measuring the AA and like other subjective methods tends to overestimate the true AA, mainly due to depth of focus, target and pupil size and illumination.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have tested the accuracy of the push-up-to-blur technique and found that illumination, target size, depth of focus, endpoint criteria, proximal cues and pupil size all affect these measurements. 4,5,6,7,8,9,10,11,12,13,14 Generally, the push-up-to-blur method overestimates the AA and can suggest that active accommodation is present when it is not. 4,5 The subjective push-up-to-blur technique overestimates the true AA of the eye due to an increase in proximally induced accommodation and the relative linear magnification of the target.…”
Section: Introductionmentioning
confidence: 99%
“…The push-up amplitude of accommodation has been known to be significantly higher than the minus-lens-to-blur amplitude of accommodation 5,26,30,32,35 and overestimates the amplitude of accommodation. 5,6,30,36 In the current study, the minuslens-to-blur amplitude of accommodation was measured with the target at 40 cm, as a study 36 found higher repeatability at this distance than at 33 cm.…”
Section: Article Informationmentioning
confidence: 67%
“…For good repeatability, the measurements must be taken under the same conditions [ 27 ]. For example, our previous study [ 28 ] demonstrated large variation in measurements of vergence and fusional reserve on various weekdays and even during the day. If accommodative amplitude measurement is repeated with a 24 h difference, the repeatability coefficient is ±1.24 at a viewing distance of 33 cm, compared to ±0.99 at a viewing distance of 40 cm [ 29 ].…”
Section: Discussionmentioning
confidence: 99%